Design of steering mechanism and control of nonholonomic trailer systems - Nakamura, Y; Ezaki, H; Tan, Y; Chung, W (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2001)
A wheeled mobile robot with trailers has been studied as a class of nonholonomic systems. It is proved that a system of a tractor and trailers with an appropriate connecting mechanism can be stabilized to desired positions via nonholonomic motion control. Trailers, on the other hand, have been developed and widely used in the industry. The main focus of industrial design is set on reducing tracking error from a reference trajectory. This paper attempts to bridge over the gap between these two approaches. We develop a design theory of trailer systems with passive steering. The designed systems show a good performance in practical path following, and accept the chained form transformation and nonlinear control strategies for nonholonomic systems.